Video analysis of acute injuries and referee decisions during the 24th Men's Handball World Championship 2015 in Qatar. (19th April 2018) - Andersson, S. H.; Cardinale, M.; Whiteley, R.; Popovic, N.; Hansen, C.; Lopez, F. S.; Bere, T.; Bahr, R.; Myklebust, G.
Abstract : Although handball is a contact sport with a high risk of acute match injuries, their mechanisms have not yet been investigated. We aimed to describe the mechanisms of acute match injuries in elite male handball and evaluate referee performance in injury situations. Based on injury surveillance from the 24th Men′s Handball World Championship 2015 in Qatar, injury situations and the referee decisions were identified on video footage. A total of 55 injury situations and 37 referee decisions were included for analysis. The injury situations were analyzed individually by five handball experts, followed by a consensus meeting. An expert referee panel performed individual blinded evaluation of the referee decisions, followed by an online consensus meeting. Injuries were evenly distributed among attackers (n = 29) and defenders (n = 26). The most frequent injury cause was contact trauma due to a tackle (n = 27). At the time of injury, attackers were most frequently performing a jump shot (n = 9), while defenders were completing a tackle (n = 10). Defenders most commonly tackled the throwing arm (n = 7) or toward the head/face region (n = 6) of injured attackers, while attackers most frequently hit injured defenders with the knee during jump shots (n = 5). Agreement between the referees and the expert panel was weak (kappa: 0.22, 95% CI 0.07 to 0.36), with substantially more lenient rule interpretation by the referees. Our results suggest that stricter refereeing and rule amendments should be considered to prevent acute match injuries in elite handball, especially in relation to tackling episodes when an attacker is performing a jump shot.